Are You a Satisfied Customer at Aeon? A Case Study in Malaysia - Kee, Daisy Mui Hung; Chze, Foo Mei; Ayuni, Farhana; Najwa, Fatin; Nadia, Farah; Yadav, Sneh; Das, Abhijit (International Journal of Tourism and Hospitality in Asia Pasific, 2022)
Due to many global marketers and global brands, retailers face many challenges. With increased competition in the retailing industry, customers typically have more retail options to choose from. As a result, retailers seek efficient ways to fulfill and meet their consumers' needs and demands. This paper aims to investigate if service quality, perceived trust, perceived convenience, and product price significantly correlate with customer satisfaction. This paper also examines if customer satisfaction leads to behavioral intention. A total of 150 Aeon customers participated in an online survey via Google Forms. This data was analyzed using SPSS. This finding revealed that service quality, perceived trust, perceived convenience, and product price have a significant relationship with customer satisfaction. The researchers also found that customer satisfaction is strongly associated with behavioral intention.  The findings show that the necessity of service quality, trust, convenience, and product price were good predictors of customer satisfaction, which in turn may lead to behavioral intention. The findings provide new insights on customer satisfaction towards Aeon Malaysia.